Infertility in Malawi: exploring its impact and social consequences - de Kok, Christina (CRFR, 2008)
Infertility is a serious personal, social and public health issue in developing countries such as Malawi. Infertility is often a ‘hidden’ problem in this context as the policy and service emphasis is on issues like infant mortality and family planning. Social expectations can also contribute to the problem. This research briefing reports on the first in-depth qualitative study of infertility in Malawi. These findings aim to form a starting point for development of services and programs that are based on people’s own views, local needs and go beyond family planning.
Keywords: Childlessness; Health, illness and promotion; Reproductive issues